2020
DOI: 10.14202/vetworld.2020.296-303
|View full text |Cite
|
Sign up to set email alerts
|

Presence probability of Hemiscorpius lepturus Peters, 1861 using maximum entropy approach in the western areas of Zagros Mountains, Iran

Abstract: Aim: The purpose of this research was to use environmental variables for predicting the probability of Hemiscorpius lepturus existence in the provinces where situated in the west of the Zagros Mountains. Materials and Methods: In this study, 64 occurrence records of the H. lepturus were extracted from the published documents available in electronic databases. MaxEnt model was used for predicting the ecological niches of this species. Normalized difference vegetation index (NDVI) and 19 climatic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Different aspects of scorpion sting have been previously studied in Iran (Pipelzadeh et al 2007, Jalali et al 2010, Moosavy et al 2016, Alinejad et al 2017, Ebrahimi et al 2018, Najafian et al 2020). But their distribution patterns and ecology have been less studied (Shahi et al 2015, 2016, Dehghani and Kassiri 2017, Hanafi-Bojd et al 2020). Only in recent years, species distribution modeling methods and GIS have been used to map the geographical distribution of Iranian scorpions (Mirshamsi 2013, Haghani et al 2020, Hanafi-Bojd et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different aspects of scorpion sting have been previously studied in Iran (Pipelzadeh et al 2007, Jalali et al 2010, Moosavy et al 2016, Alinejad et al 2017, Ebrahimi et al 2018, Najafian et al 2020). But their distribution patterns and ecology have been less studied (Shahi et al 2015, 2016, Dehghani and Kassiri 2017, Hanafi-Bojd et al 2020). Only in recent years, species distribution modeling methods and GIS have been used to map the geographical distribution of Iranian scorpions (Mirshamsi 2013, Haghani et al 2020, Hanafi-Bojd et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…But their distribution patterns and ecology have been less studied (Shahi et al 2015, 2016, Dehghani and Kassiri 2017, Hanafi-Bojd et al 2020). Only in recent years, species distribution modeling methods and GIS have been used to map the geographical distribution of Iranian scorpions (Mirshamsi 2013, Haghani et al 2020, Hanafi-Bojd et al 2020). In the present study, however, for the first time, villages at risk of scorpion stings were identified and mapped.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that mean temperature of the wettest quarter (Bio8) and precipitation during the coldest quarter (Bio19) affected the desirability of habitat for Odontobuthus doriae and Scorpio maurus, receptively (Haghani et al 2020). In addition, MaxEnt modeling showed that the most important environmental factor influencing the distribution of Hemiscorpius lepturus was the maximum temperature of the warmest month (Bio5) (Hanafi-Bojd et al 2020). According to Chowell et al (2005), climatic conditions, dryness and heat are factors that increase the threat of being stung by a scorpion.…”
Section: Discussionmentioning
confidence: 99%